Prospective Risk of Stillbirth and Neonatal Complications in Twin Pregnancies: Systematic Review and Meta-analysis. Issue 1 (January 2017) - Cheong-See, Fiona; Schuit, Ewoud; Arroyo-Manzano, David; Khalil, Asma; Barrett, Jon; Joseph, K. S.; Asztalos, Elizabeth; Hack, Karien; Lewi, Liesbeth; Lim, Arianne; Liem, Sophie; Norman, Jane E.; et al.
Abstract : (Abstracted from BMJ 2016;354:i4353) Twin pregnancies are at increased risk of stillbirth. Uncomplicated twin pregnancies are commonly delivered earlier to prevent stillbirth; however, there is a risk of neonatal complications associated with being born prior to 39 weeks' gestation.